ON POINTWISE ?-STATISTICAL CONVERGENCE OF ORDER ? OF SEQUENCE OF FUNCTIONS - Et, Mikail; Cinar, Muhammed; Karakas, Murat (World Scientific Publ Co Pte Ltd, 2013)
In this study, we introduce the concepts of pointwise lambda-statistical convergence of order a and pointwise [V, lambda]-summability of order alpha of sequences of real valued functions. Some relations between S-lambda(alpha)(f)-statistical convergence and strong w(lambda p)(alpha)(f)-summability are given.
Keywords: Statistical convergence; sequences of function; Cesaro summability